Femtosecond Laser–Assisted Descemetorhexis: A Novel Technique in Descemet Membrane Endothelial Keratoplasty. Issue 10 (October 2016) - Pilger, Daniel; von Sonnleithner, Christoph; Bertelmann, Eckart; Joussen, Antonia M.; Torun, Necip
Abstract : Purpose: To explore the feasibility of femtosecond laser–assisted descemetorhexis (DR) to facilitate Descemet membrane endothelial keratoplasty (DMEK) surgery. Methods: Six pseudophakic patients suffering from Fuchs' endothelial dystrophy underwent femtosecond laser–assisted DMEK surgery. DR was performed using the LenSx femtosecond laser, followed by manual removal of the Descemet membrane. Optical coherence tomography images were used to measure DR parameters. Patients were followed up for 1 month to examine best corrected visual acuity, endothelial cell loss, flap detachment, and structure of the anterior chamber of the eye. Results: The diameter of the DR approximated the intended diameter closely [mean error of 34 μm (0.45%) and 54 μm (0.67%) in the x- and y-diameter, respectively] and did not require manual correction. The median visual acuity increased from 0.4 logMAR (range 0.6–0.4 logMAR) preoperative to 0.2 logMAR (range 0–0.4 logMAR) postoperative. The median endothelial cell loss was 22% (range 7%–34%). No clinically significant flap detachments were noted. All patients had clear corneas after surgery, and no side effects or damage to structures of the anterior chamber were noted. Conclusions: Femtosecond laser–assisted DR is a safe and precise method for facilitating DMEK surgery.